2008
DOI: 10.1093/cercor/bhn041
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of Human Striatum: A Resting State fMRI Study

Abstract: Classically regarded as motor structures, the basal ganglia subserve a wide range of functions, including motor, cognitive, motivational, and emotional processes. Consistent with this broad-reaching involvement in brain function, basal ganglia dysfunction has been implicated in numerous neurological and psychiatric disorders. Despite recent advances in human neuroimaging, models of basal ganglia circuitry continue to rely primarily upon inference from animal studies. Here, we provide a comprehensive functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

189
972
7
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 994 publications
(1,171 citation statements)
references
References 100 publications
189
972
7
3
Order By: Relevance
“…Supporting Information Figure S4a shows group average maps of the SSCs that were most strongly connected with the PCG, MFG, OFG, or inferior parietal lobule, based on the atlas by Desikan et al (2006). Consistent with previous studies (Barnes et al, 2010; Choi et al, 2012; Di Martino et al, 2008; Draganski et al, 2008; Garcia‐Garcia et al, 2018; Janssen et al, 2015; Jaspers et al, 2017; Jung et al, 2014), the middle part of the putamen was most strongly connected with the PCG, the caudate nucleus was most strongly connected with the MFG, and the caudate nucleus extending to ventral striatum was most strongly connected with the OFG.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Supporting Information Figure S4a shows group average maps of the SSCs that were most strongly connected with the PCG, MFG, OFG, or inferior parietal lobule, based on the atlas by Desikan et al (2006). Consistent with previous studies (Barnes et al, 2010; Choi et al, 2012; Di Martino et al, 2008; Draganski et al, 2008; Garcia‐Garcia et al, 2018; Janssen et al, 2015; Jaspers et al, 2017; Jung et al, 2014), the middle part of the putamen was most strongly connected with the PCG, the caudate nucleus was most strongly connected with the MFG, and the caudate nucleus extending to ventral striatum was most strongly connected with the OFG.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies of striatal functional architecture have revealed a well‐organized relationship for cerebrocortical‐striatal connectivity (Barnes et al, 2010; Choi et al, 2012; Di Martino et al, 2008; Draganski et al, 2008; Garcia‐Garcia et al, 2018; Janssen et al, 2015; Jaspers et al, 2017; Jung et al, 2014). We confirmed, as a positive control, that the larger‐scale observations could be replicated using the present data set.…”
Section: Resultsmentioning
confidence: 98%
“…Given our a priori hypothesis that PD22 and dyskinesias23 would be associated with abnormal activity of the putamen, we defined the bilateral dorsocaudal putamen as a region of interest (ROI) and applied small volume correction (SVC) using a sphere 10mm in radius on the Montreal Neurologic Institute coordinates ±28, 2, 2 (x, y, z) 24…”
Section: Methodsmentioning
confidence: 99%
“…Striato-cortico-striatal loops predominantly involving prefrontal cortex (PFC) projections have been delineated in nonhuman primates (Alexander et al, 1986), and confirmed in humans with diffusion tensor imaging (Leh et al, 2007;Lehericy et al, 2004) and resting-state functional magnetic resonance imaging (rs-fMRI) (Di Martino et al, 2008). These loops include: a ventral circuit anchored in the inferior limbic subdivision of the striatum and comprising connections with orbitofrontal cortex (OFC), ventromedial PFC, medial thalamus, and limbic regions that is fundamental to associative learning and reward-mediated decision making (Knutson and Cooper, 2005); and a dorsal circuit, including the associative subdivision of the striatum, dorsolateral PFC and mediodorsal and ventroanterior thalamus that maintains information relating to reward outcomes (O' Doherty et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Seeds were defined in both hemispheres as 3.5 mm radius spheres at the following stereotaxic coordinates: dorsal caudate (DC; x = ± 13, y = 15, z = 9); ventral striatum/nucleus accumbens (VS; x = ± 9, y = 9, z = − 8); dorsal-caudal putamen (dcP; x = ± 28, y = 1, z = 3); and ventral-rostral putamen (vrP; x = ± 20, y = 12, z = − 3) (Dandash et al, 2014). To complement the original investigation of Di Martino et al (2008), effects were additionally modeled in relation to their remaining two seeds, but as per previous work (Dandash et al, 2014), experimental focus was placed upon the former four seeds. Component-based correction (CompCor) of temporal confounds relating to head movement and physiological noise was performed using the CONN toolbox (v.14) (Whitfield-Gabrieli and Nieto-Castanon, 2012).…”
Section: Fmri Analysismentioning
confidence: 99%